Biological safety : principles and practices - Wooley, Dawn P.; Byers, Karen B. (ASM Press, 2017)
Biological safety and biosecurity protocols are essential to the reputation and responsibility of every scientific institution, whether research, academic, or production. Every risk-no matter how small-must be considered, assessed, and properly mitigated. If the science is not safe, it is not good science. Now in its fifth edition, Biological Safety: Principles and Practices remains the most comprehensive biosafety reference.